A questão social e as alternativas da sociedade civil no contexto das novas formas de governação - Silva Ferreira (Ciências Sociais Unisinos, 2008)
In this paper, I discuss the meaning and role of civil society in the context of transformations in contemporary societies, mainly in terms of the governance of the social problems that are conceived in terms of the social question. I suggest a relational definition of civil society as mediator between the demands and needs of the life world and the social systems. I discuss the modern boundaries between state, economy, community and society and the relationship between civil society, these boundaries and it questioning. Finally, I problematize the meaning of civil society in contexts of hybridization and network governance and the challenges for a new meaning and a new role.